The Concept of Merdeka Belajar in Early Childhood: Comparative Study of Reggio Emilia and Ki Hajar Dewantara's Thoughts - Aisyah Nurul Hurriyah Sani; Safariyatul Mahmudah; Ali Akbar Muhammad (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2022)
This study aims to examine the concept of independent learning for early childhood according to Reggio Emilia and Ki Hajar Dewantara, to find out the implications of independent thinking of learning for early childhood on current education, to find similarities and differences in the concept of independent learning to learn in early childhood education according to Reggio Emilia and Ki Hajar Dewantara. This is important considering that Ki Hajar Dewantara is a figure known as the Father of National Education and Reggio Emilia, who was once named one of the best early childhood education schools in the world. The two elements of the educational approach can be collaborated and investigated with comparative qualitative research methods to compare or find similarities from concepts or data drawn to new conclusions using historical, pedagogical, and comparative approaches. In this study, the stages of data analysis are data reduction, data display, focus group discussion, verification, and conclusion drawing. The results show that the concept of independent learning for early childhood is intended to reduce the impact of the decline in student learning performance after COVID-19, with the contextual nature of the independent learning curriculum that can be applied according to different environmental conditions in each school. The implications of the concept of independent learning Reggio Emilia and Ki Hajar Dewantara use the philosophy of constructivism, which assumes that an individual builds learning knowledge based on objects, phenomena, experiences, and their environment. The opportunity to learn both approaches is made through games and art. Both approaches have similarities and strengths with the arts and the philosophical agreement that children learn through play by providing an engaging environment. While Reggio Emila's approach uses the term image of the child, which believes that children are individuals who are capable of doing things independently and with minimal interruptions from adults, Ki Hajar Dewantara uses the Among system through this, the teacher has a significant role to be a role model for children. Both figures have their respective points of view, but it does not become an inequality in the education system. Both views can be alternative considerations for the development of education.